Reasons for Aggravating and Mitigating Punishment for International Crimes- An Analytical Study - Asaeed, Zana Rafeeq; Qadir, Barzi Abdulbaqi (Journal of Legal and Political Studies, 2021)
The circumstances of the crime are considered as means of legislative and judicial individualization of punishment, and the crimes differ according to the circumstances of each crime in terms of the amount of punishment, and if they agreed in the criminal outcome, the covenant in which the punishment was determined in an abstract manner has ended without concern for the material or personal conditions related to the commission of the crime. These situations play an important role in making the punishment more realistic or more responsive to the circumstances of the offender and the circumstances of the crime, and ultimately lead to a just punishment. The penalty is required to be proportional to the crime, because the penalty must be just and fulfill its function in society, and the burden of proving proportionality falls on the legislator, who, when setting the penalty, must take into account its quantitative and qualitative compatibility with the gravity of the criminal incident. and the International Criminal Court takes into account several things when determining the amount of punishment to be inflicted and applied to the convicted person, such as the harm done, or the harm suffered by the victim or his family, as well as the nature of the illegal behavior committed and the means used to commit the crime, and the extent of the person’s participation the convict, the extent of intent, the circumstances relating to the manner, place and time, the age of the convicted person, his education, and his social and economic status
Keywords: circumstances of the crime; covenant; punishment; individualization of punishment; economic status